DIGITAL LIBRARY EMPOWERMENT IN INFORMATION FULFILLMENT AT THE STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA - Mucklis Mucklis; Suwardi Lubis; Rubino Rubino (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This article discusses the transformation of a traditional library into a digital library at the State Islamic University of North Sumatra (UINSU). This shift in library function is a demand for technological advancements, so that the scientific world evolves in tandem with technology. The goal of this article is to learn about the features of the UINSU digital library and how to use them. This article's methodology is descriptive qualitative, with data collected through interviews, observations, and documentation. In order to highlight the process and meaning in qualitative research, the authors process the data using narrative analysis to describe the phenomena that occur. UINSU digital library empowerment has been available since November 16, 2021 via the library.uinsu.ac.id website, which includes opac, electronic journals, electronic books, archives of scientific works by the UINSU academic community, and classic books on the ideas of Middle Eastern scholars.